First-generation clinical dual-source photon-counting CT: ultra-low-dose quantitative spectral imaging - Liu, Leening P.; Shapira, Nadav; Chen, Andrew A.; Shinohara, Russell T.; Sahbaee, Pooyan; Schnall, Mitchell; Litt, Harold I.; Noël, Peter B. (European radiology, 2022)
Objective Evaluation of image characteristics at ultra-low radiation dose levels of a first-generation dual-source photon-counting computed tomography (PCCT) compared to a dual-source dual-energy CT (DECT) scanner. Methods A multi-energy CT phantom was imaged with and without an extension ring on both scanners over a range of radiation dose levels (CTDI vol 0.4–15.0 mGy). Scans were performed in different modes of acquisition for PCCT with 120 kVp and DECT with 70/Sn150 kVp and 100/Sn150 kVp. Various tissue inserts were used to characterize the precision and repeatability of Hounsfield units (HUs) on virtual mono-energetic images between 40 and 190 keV. Image noise was additionally investigated at an ultra-low radiation dose to illustrate PCCT’s ability to remove electronic background noise. Results Our results demonstrate the high precision of HU measurements for a wide range of inserts and radiation exposure levels with PCCT. We report high performance for both scanners across a wide range of radiation exposure levels, with PCCT outperforming at low exposures compared to DECT. PCCT scans at the lowest radiation exposures illustrate significant reduction in electronic background noise, with a mean percent reduction of 74% ( p value ~ 10 −8 ) compared to DECT 70/Sn150 kVp and 60% ( p value ~ 10 −6 ) compared to DECT 100/Sn150 kVp. Conclusions This paper reports the first experiences with a clinical dual-source PCCT. PCCT provides reliable HUs without disruption from electronic background noise for a wide range of dose values. Diagnostic benefits are not only for quantification at an ultra-low dose but also for imaging of obese patients. Key Points PCCT scanners provide precise and reliable Hounsfield units at ultra-low dose levels. The influence of electronic background noise can be removed at ultra-low-dose acquisitions with PCCT. Both spectral platforms have high performance along a wide range of radiation exposure levels, with PCCT outperforming at low radiation exposures.